Sistem Pengelolaan Kawasan Ekowisata Gunung Gamalama di Pulau Ternate - Muslim Fadel (Tekstual, 2018)
Ecotourism is a form of special interest tourism activity that is a responsibletravel to natural areas which conserve the environment and improve local people’swelfare by involving active participation of people nearby the area in form of sustainablemanagement.This study focuses on management system of 3A (attractions, amenity,accessibility) and the promotion of community-based ecotourism nearby GamalamaMountain. There are three sites of ecotourism observed. They are Batu Angus,Sulamadaha Beach, and Tolire Lake. The objectives of this study are: (1) Tocomprehend the management system of 3A (attractions, amenity, accessibility) and thepromotion of community-based ecotourism in the three sites (Batu Angus, SulamadahaBeach, Tolire Lake) nearby Gamalama Mountain. (2) To analyze the managementsystem of 3A (attractions, amenity, accessibility) and the promotion of communitybasedecotourism in the three sites (Batu Angus, Sulamadaha Beach, Tolire Lake)located nearby Gamalama Mountain.The method of research is conducted through survey and in-depth interviewsusing qualitative and quantitative approaches. The data used in this research consist ofprimary and secondary data. The primary data sources from observation, in-depthinterviews, and direct documentation. Secondary data is derived from documentationanalysis that relates to the geographical position, vast of area, climate, topography, anddemography.The results of this study presents that the management system of 3A (attractions,amenity, accessibility) and the promotion of community-based ecotourism in the threesites (Batu Angus, Sulamadaha Beach, Tolire Lake) have not been conducted optimally.It is caused by some factors such as limited human resources in the field of tourism, lackof funding, lack of cooperation among government, private and public sectors, as well asthe lack of socialization on tourism awareness from Department of Culture and Tourismof Ternate that influence public’s low awareness of tourism.